2020
DOI: 10.1186/s12944-020-01250-6
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of nutraceuticals and natural products on small dense LDL levels, LDL particle number and LDL particle size: a clinical review

Abstract: Cardiovascular diseases (CVDs) are globally the major causes of morbidity and mortality. Evidence shows that smaller and denser low-dense lipoprotein (sdLDL) particles are independent atherogenic risk factors for CVD due to their greater susceptibility to oxidation, and permeability in the endothelium of arterial walls. sdLDL levels are an independent risk factor and of more predictive value than total LDL-C for the assessment of coronary artery disease and metabolic syndrome. Functional food ingredients have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 121 publications
(117 reference statements)
0
38
0
2
Order By: Relevance
“…Omega-3 (ω-3) polyunsaturated fatty acids, which include eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have varied roles in human health and disease. 181 Deficiency in ω-3 fatty acids is associated with chronic diseases. One study demonstrated that pretreatment of LPS-primed BMDMs with DHA and EPA inhibited inflammasome activation and IL-1β secretion.…”
Section: ω-3 Fatty Acids Negatively Regulate Inflammasomesmentioning
confidence: 99%
“…Omega-3 (ω-3) polyunsaturated fatty acids, which include eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), have varied roles in human health and disease. 181 Deficiency in ω-3 fatty acids is associated with chronic diseases. One study demonstrated that pretreatment of LPS-primed BMDMs with DHA and EPA inhibited inflammasome activation and IL-1β secretion.…”
Section: ω-3 Fatty Acids Negatively Regulate Inflammasomesmentioning
confidence: 99%
“…A current tendency of the world population is focused on consuming natural foods derived from plants with high nutritional value (Román-Cortés et al, 2018;Orozco-Sifuentes et al, 2019;Ramírez-Jaspeado et al, 2020) and prebiotic properties (Talebi et al, 2020). Stenocereus queretaroensis (Cactaceae) is a plant endemic to Mexico (Campos-Rojas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…SdLDL is a particle with a speci c density of 1.044-1.063 g/ml and a size of 19.0-20.5 nm [9,17]. As compared with lbLDL, sdLDL particles have lower a nity to the LDL receptor, and longer retention time in the circulation.…”
Section: Correlations Among Lipidsmentioning
confidence: 99%
“…More recently, LDL-C has been subdivided into granular fractions, among which small dense LDL-C (sdLDL-C) with a smaller particle size has attracted attention as a lipid marker that may be more sensitive for predicting CV events than LDL-C [7,8]. LDL-C with a smaller particle size is more easily oxidized and permeable to the cell wall [9], promoting atherosclerotic changes more than LDL-C with a larger particle size, so called large buoyant LDL-C (lbLDL-C). Several studies, including the Atherosclerosis Risk in Communities (ARIC) study, have reported sdLDL-C as a more sensitive predictive marker of CV events as compared with LDL-C [8].…”
Section: Introductionmentioning
confidence: 99%